Hands-off? Laissez-faire policies on Covid-19 may exacerbate health inequalities. Issue 3 (1st July 2020) - Foley, William; Gërxhani, Klarita
Abstract : Purpose: This paper establishes an association between income and the likelihood of seeking medical treatment for Covid-19 symptoms in some countries. We provide an explanation for this income effect based on the stringency of government response to the pandemic and the unequal distribution of agency among social classes. Design/methodology/approach: The paper makes use of data from the Six-Country Survey on Covid-19 to establish the existence of an income effect on health utilisation, and from the Oxford Covid-19 Government response tracker to show that this income effect is associated with the stringency of governmental response to the pandemic. Data from the 2011/12 "Health and Healthcare" round of the International Social Survey Programme is used to show that this income effect cannot be explained by pre-existing patterns. An explanation for the link between government stringency and the income effect is advanced on a theoretical basis. Findings: The authors find in Britain, the US, and – with greater uncertainty – in Japan that individuals who experience potential Covid-19 symptoms are less likely to seek medical treatment if they have a lower income. The authors also show that governments in these countries adopted a less stringent response to the pandemic than the countries in our sample which do not exhibit an income effect – China, Italy and South Korea. The authors argue that laissez-faire policies place the burden of action upon the individual, activating underlying differences in agency between the social classes, and making (high) low-income individuals (more) less likely to seek medical attention. Research limitations/implications: Since there was not a direct measure of agency in the data, it could not be empirically verified that agency mediates the effect of government stringency on health utilisation. Further research could make use of datasets which incorporate such a measure, if they become available. It could also extend the geographical scope of the findings, to see if the income effect manifests in other countries which adopted a laissez-faire response to the pandemic. Practical implications: Governments should intervene more stringently during pandemics to minimise inequality in health outcomes. Originality/value: This paper establishes an association between the stringency of government response to the Covid-19 pandemic and income inequality in health utilisation. This contributes to scholarly and policy debates around health inequality in the area of social epidemiology, and the sociology of inequality more generally. It is also of relevance to the general public, in the context of a deadly pandemic.